Hospital Waste and Cleaning Workers in Baquba Teaching Hospital - Al-Azzawi , Shahab A (Diyala Journal of Medicine, 2019)
Background: Medical waste is potentially hazardous, infectious, and toxic materials. It therefore requires special handling and disposal practices. Aims: To determine: Impact of medical waste upon cleaning workers. Awareness of cleaning workers toward medical waste in Baquba teaching hospital Subjects and Methods: A cross-sectional study was conducted among a random sample of (80) employees in Baquba teaching hospital in May 2011. Self-administered questionnaire which included occupational, organisational factors and sociodemographic variables was used. In addition, researcher observed collection, segregation, transportation, and disposal of medical waste at the hospital. Result: Most of the cleaning workers are younger age (35 year ), male 85%, the rate of illiteracy among cleaners in the hospitals was high 47.5%, the highest level of knowledge about hazard categories of medical waste had worked for (2–5 years), the cleaners are focused mainly on the sharps particles first degree, percentage who reported sharps as medical waste about 98%. Conclusion: Most cleaning workers lacked sufficient awareness of impacts of poor clinical waste disposal and had never heard of any policy national or international on safe clinical waste management. Methods of collecting, segregating, transporting and disposing clinical waste at the hospital was poor.